2023
DOI: 10.1111/jog.15714
|View full text |Cite
|
Sign up to set email alerts
|

SIK2: A critical glucolipid metabolic reprogramming regulator and potential target in ovarian cancer

Abstract: Aim To explore the role of salt‐inducible kinase 2 (SIK2) on glucose and lipid metabolism in ovarian cancer (OC), so as to increase the understanding of potential inhibitors targeting SIK2 and lay a foundation for future precision medicine in OC patients. Methods We reviewed and summarized the regulation effect of SIK2 on glycolysis, gluconeogenesis, lipid synthesis, and fatty acids β‐oxidation (FAO) in OC, as well as the potential molecular mechanism and the prospects of potential inhibitors targeting SIK2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Hu's study concluded that SIK2 not only enhances the Warburg effect by promoting glycolysis, inhibiting oxidative phosphorylation and gluconeogenesis, but also regulates intracellular lipid metabolism by promoting lipid synthesis and FAO. Ultimately, this leads to growth, proliferation, invasion, metastasis and therapeutic resistance in OC 122 . Additionally, molecules such as HSP70, SATB1, PSMD14, and STAT3 regulate glucose metabolism through different mechanisms or signaling cascades in OC, which promotes cancer progression and results in poor prognosis 84 , 87 , 94 , 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Hu's study concluded that SIK2 not only enhances the Warburg effect by promoting glycolysis, inhibiting oxidative phosphorylation and gluconeogenesis, but also regulates intracellular lipid metabolism by promoting lipid synthesis and FAO. Ultimately, this leads to growth, proliferation, invasion, metastasis and therapeutic resistance in OC 122 . Additionally, molecules such as HSP70, SATB1, PSMD14, and STAT3 regulate glucose metabolism through different mechanisms or signaling cascades in OC, which promotes cancer progression and results in poor prognosis 84 , 87 , 94 , 95 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several neurological functions have recently been reported to be controlled by SIK, including circadian rhythmicity. In addition, an imbalance in SIK function has been associated with several types of cancer ( 3 , 4 , 5 , 6 ). Although the three SIK isoforms share similar structures and targets, they play both distinct and redundant roles in regulating physiological processes.…”
mentioning
confidence: 99%